18β-Glycyrrhetinic Acid Inhibits Osteoclastogenesis In Vivo and In Vitro by Blocking RANKL-Mediated RANK–TRAF6 Interactions and NF-κB and MAPK Signaling Pathways - Chen, Xiao; Zhi, Xin; Yin, Zhifeng; Li, Xiaoqun; Qin, Longjuan; Qiu, Zili; Su, Jiacan (Frontiers in Pharmacology, 2018)
Bone metabolism is determined by a delicate balance between bone resorption by osteoclasts and bone formation by osteoblasts. The imbalance due to over-activated osteoclasts plays an important role in various diseases. Activation of NF-κB and MAPK signaling pathways by receptor activator of nuclear factor -κB ligand (RANKL) is vital for osteoclastogenesis. Here we for the first time explored the effects of 18β-glycyrrhetinic acid (18β-GA), a pentacyclic triterpenoid found in the Glycyrrhiza glabra L roots, on RANKL-induced osteoclastogenesis, osteoclast functions and signaling pathways in vitro and in vivo. In bone marrow monocytes (BMMs) and RAW264.7 cells, 18β-GA inhibited osteoclastogenesis, decreased expression of osteoclastogenesis-related genes, including TRAP, cathepsin K, CTR and MMP-9, blocked actin ring formation and compromised osteoclasts functions in a dose-dependent manner at an early stage with minimal effects on osteogenic and adipogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). For underlying molecular mechanisms, 18β-GA inhibited RANKL-induced phosphorylation of p65, p50, and IκB, blocked p65 nuclear translocation and decreased the DNA-binding activity of NF-κB. Besides, 18β-GA inhibited the activation of the MAPK pathways. Co-immunoprecipitation showed that 18β-GA treatment blocked RANK-TRAF6 association at an upstream site. In vivo, 18β-GA treatment inhibited ovariectomy-induced osteoclastogenesis and reduced bone loss in mice. Overall, our results demonstrated that 18β-GA inhibited RANKL-induced osteoclastogenesis by inhibiting RANK expression in preosteoclasts and blocking the binding of RANK and TRAF6 which lead to the inhibition of NF-κB and MAPK signaling pathways. 18β-GA is a promising novel candidate in the treatment of osteoclast-related diseases such as postmenopausal osteoporosis.